2018
DOI: 10.1071/cp18049
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of post-drought recovery, persistence and summer dormancy in orchardgrass (Dactylis glomerata)

Abstract: The genetic basis of post-drought recovery, summer dormancy and persistence under drought stress is little investigated in orchardgrass (Dactylis glomerata L.). In this study, polycross populations (half-sib genotypes) were evaluated under normal and regulated deficit irrigation for 3 years (2012–14) in the field. Irrigation was then withheld in 2015, and the genotypes were evaluated for post-drought recovery and persistence. The results showed that regulated deficit irrigation decreased forage yield, yield co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Although we could not demonstrate a strong relationship between PE and drought recovery in the field, most of the genotypes with positive PE were able to recover after intense drought stress. Our results were consistent with other studies (Pirnajmedin et al., 2018). According to our findings, genotypes 1M, 3M and 4E had the longest PE, and genotypes 3L, 15L and 25L had the lowest PE amongst 21 different tall fescue genotypes under different conditions.…”
Section: Discussionsupporting
confidence: 94%
“…Although we could not demonstrate a strong relationship between PE and drought recovery in the field, most of the genotypes with positive PE were able to recover after intense drought stress. Our results were consistent with other studies (Pirnajmedin et al., 2018). According to our findings, genotypes 1M, 3M and 4E had the longest PE, and genotypes 3L, 15L and 25L had the lowest PE amongst 21 different tall fescue genotypes under different conditions.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with our findings, some previous studies in different forage grass species such as tall fescue have reported the moderate to high narrow-sense heritability for yield-related trait [22,33,34]. Pirnajmedin et al [35] reported moderate to high values of heritability for persistence (0.54) and summer dormancy index (0.64) in orchardgrass (Dactylis glomerata L.). However, little literature is still available on the heritability of summer dormancy index and persistence in different perennial grass species.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, a wide range of narrow‐sense heritability has been reported for forage yield and yield components (such as CD, PH, and NS) in other grass species (Araghi et al., 2014; Jafari & Naseri, 2007). A moderate to high value of narrow sense heritability was reported for recovery yield (0.59) in orchardgrass and smooth bromegrass (0.69) (Pirnajmedin et al., 2018; Saeidnia et al., 2019). Saeidnia et al.…”
Section: Discussionmentioning
confidence: 99%
“…The most important survival strategies in perennial grasses include not only conservation of production during drought, but also the capacity to survive and recover quickly after re‐watering (Pirnajmedin et al., 2018; Abdollahi et al., 2019). Therefore, it is important to have information about genetic variability and inheritance of yield productivity, post‐drought recovery, and their related traits to identify superior genotypes with possible utility in specific breeding programs (Majidi et al., 2009; Pirnajmedin et al., 2018). In this study, considerable genetic variation was observed among HS families for all of the traits, indicating that selection of genotypes with variable yield performance, recovery potential, and drought tolerance is possible through HS mating.…”
Section: Discussionmentioning
confidence: 99%